2014
DOI: 10.1179/1362171813y.0000000192
|View full text |Cite
|
Sign up to set email alerts
|

Orientation relationships of intragranular austenite in duplex stainless steel weld metals

Abstract: Formation and characteristics of fine intragranular austenite were studied for low energy input duplex stainless steel welds. Microstructures were largely ferritic with some allotriomorphic grain boundary austenite, Widmansta ¨tten type austenite, fine intragranular austenite and nitrides. Electron backscattered diffraction analysis revealed that grain boundary austenite had a random orientation relationship (OR) with one of the adjacent ferrite grains and was close to Kurdjumov-Sachs (KS) with the other, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…[17][18][19][20] The cooling rate of RSW is significantly higher than that of the conventional arc welding processes. Gould et al 21 proposed a simple analytical model predicting cooling rates of resistance spot welds, as follows…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] The cooling rate of RSW is significantly higher than that of the conventional arc welding processes. Gould et al 21 proposed a simple analytical model predicting cooling rates of resistance spot welds, as follows…”
Section: Introductionmentioning
confidence: 99%
“…Also, the thickness of austenite layers was thin when compared to higher heat inputs and fails at 11,600 N. When the heat input is increasing further to 365.57 J, WA and increase of IGA was observed in the fusion zone. It may be the fact due to faster cooling rate 29 as shown in Figure 6 and fails at 12,100 N. Furthermore, the heat input was increased to the maximum level that is 820.03 J and observed that the thickness of austenite layer was increased with fine equiaxed grains and fails at 17,600 N. From the above discussion, the microstructure of weldments revealed that WMZ is dominated by increasing austenite layers with higher heat inputs. Also, for better clarification of this statement SEM (Scanning Electron Microscopy) test has been conducted at WMZ.…”
Section: Resultsmentioning
confidence: 82%
“…Therefore, according to the calculated deviations from the exact K–S orientation, the phase boundaries of austenite and ferrite in DSS are divided into two types. Karlsson and Börjesson [17] revealed that the phase boundaries close to K–S orientation (within 6°) are special phase boundaries (SPB) and the phase boundaries with angles larger than 6° are random phase boundaries (RPB).…”
Section: Resultsmentioning
confidence: 99%